A LEGAL ASPECTS OF LAND DISPUTES FOR SALE OF OTHER COMPANIES - J.E. Melky Purba (Jurnal Scientia, 2023)
Problems Land disputes are problems that are not easy to solve and must be resolved well, where company property is joint property of a group that is related by blood and inherited from generation to generation from previous ancestors. Buying and selling according to customary law is exchange and is in the form of what is called cash or cash. The problem is that ulayat land (high heritage) cannot be bought and sold based on West Sumatra Regional Regulation Number 6 of 2008 concerning ulayat land and its use. This paper describes the scope of regulations according to Decision number 11/Pdt.G/2015/PN.BSK, what factors are the causes of company property land disputes and how to resolve disputes over high heritage land being sold and purchased as determined by the District Court. Descriptive research using a qualitative approach and types of normative legal research and empirical juridical approaches (sociology). The data collection technique uses primary data, namely observation and secondary data, namely obtained from statutory regulations, books, scientific works related to this research, legal dictionaries, official documents and regulations.